Ações de responsabilidade social das empresas - a percepção do consumidor e sua influência na motivação de compra: o caso O Boticário - Oliveira, José Antônio Ferreira de (2002)
The social responsibility is being very considered by the organizations and it has been exercising important impact in your strategies. More companies are confronting if with the obligation of incorporating, spontaneously or for pressure of groups and segments, the social responsibility to your profit objectives. Although some defend that the responsibility of the private companies in the public area is limited to the payment of taxes and the execution of the laws, they increase the arguments that your role cannot be restricted to that field, even for a subject of survival of the own companies. It is believed that the consumers passed to value behaviors in that sense and to prefer products of identified companies as ethics and socially responsible. Besides, it is believed that with that performance socially concemed, the company develops values and practices with positive effects on your productive chain and your collaborators, generating better results. The present study had for objective to verify the social actions practiced by O Boticário they are noticed by your consuming public to the point of to take them the purchase decision. The mischievous field research to effect allowed to conclude that such actions are not noticed by your consumers and, therefore, it doesn't motivate them the purchase of the products of the company